Ocena częstości występowania czynników ryzyka zwyrodnienia plamki związanego z wiekiem - Białek-Szymańska, Anna; Misiuk-Hojło, Marta; Witkowska, Kamila (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Age-related macular degeneration (AMD) is a leading cause of irreversible loss of central vision in developing countries. Study of risk factors seems to be more significant because of the lack of effective treatment. Exact recognition especially of modifiable risk factors of AMD development could increase prevention and decrease development and progression. The aim of our study was to evaluate selected modifiable and non-modifiable risk factors of AMD. The examination included 44 AMD patients and 30 healthy subjects in control group. In both groups age, sex, eye color, smoking, UV exposition, blood pressure, cholesterol level, type of diet, family history of AMD and cataract surgeries in anamnesis, were defined. The most significant risk factors of AMD development, in presented study were female gender and UV exposition. They increased a risk accordingly 1.55 and 3 times. Iris color and low vitamin and high fat intake in diet were also essential. There was no dependence on approved risk factor such smoking and AMD appearance.